Analisis Pemahaman Matematis Siswa Sekolah Dasar melalui Aplikasi Quizizz - Bunga Nur Fadillah; Deni Adi Putra; Fajar Setiawan (Dawuh Guru: Jurnal Pendidikan MI/SD, 2023)
This article aims to analyze the mathematical understanding of grade I elementary school students using the Quizizz application media in mathematics lessons. The study in this article is focused on the mathematical understanding of elementary school students in using the Quizizz application in mathematics lessons. This research method uses a qualitative descriptive method, the data source consists of the results of interviews with teachers using teacher interview sheets, student observations using student observation sheets, and documentation. Data analysis used in this research is data collection, data reduction, data presentation, and conclusions. The focus in this research is to analyze students' systematic understanding in using the quizizz application. Based on the data obtained during the research using the quizizz application for class 1 students at SD Muhammadiyah 24 Surabaya, it shows that students are able to fulfill the four indicators of mathematical understanding including students are able to mention the concept of the material being studied, students are able to apply concepts algorithmically, students are able to identify and make examples of concepts that have been studied, and students are able to associate mathematical concepts with external and internal mathematical concepts. In addition, in this study, researchers found an increase in interest in learning as evidenced by the enthusiasm of students when working on the questions given on Quizizz. Overall students can answer correctly so that they show good understanding, but there are several obstacles to students, namely there are students who cannot read so the teacher must provide assistance to these students. So it can be concluded that grade 1 students at SD Muhammadiyah 24 Surabaya are able to understand mathematical concepts so that students' mathematical understanding is achieved according to the indicators of mathematical understanding